2011
DOI: 10.1155/2011/583981
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Acute Rejection on Kidney Allograft Outcomes in Recipients on Rapid Steroid Withdrawal

Abstract: Background. Our aim was to study the impact of clinical acute rejection (CR) and subclinical rejection (SR) on outcomes in kidney transplant recipients treated with rapid steroid withdrawal (RSW). Methods. All patients who received a living or deceased donor kidney transplant and were treated with RSW were included. The primary outcome was death-censored graft survival. Biopsies with Banff borderline changes were included with the rejection groups. Results. 457 kidney transplant recipients treated with RSW w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…Palomar reported that untreated BL-R often failed to recover to baseline. 22 Immune-mediated tubular damage was commonly observed at the time of BL-R index biopsy, 19,20,[23][24][25][26] within 40 days, 18 echoing other studies. 9,11,12,26,28,29 We found that…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Palomar reported that untreated BL-R often failed to recover to baseline. 22 Immune-mediated tubular damage was commonly observed at the time of BL-R index biopsy, 19,20,[23][24][25][26] within 40 days, 18 echoing other studies. 9,11,12,26,28,29 We found that…”
Section: Discussionmentioning
confidence: 67%
“…26,30,31 One sobering result was the poor performance of conventional anti-T cell therapy involving pulse corticosteroids to promptly control BL-R (and A-TCMR). Interstitial inflammation persisted after 9,17,19,20,23,25,26 Schweitzer found that inflammation was un- Subclinical BL-R detected by protocol biopsy is a more problematic entity, and contrary to assumption, was not entirely benign:…”
Section: Bl-r (And A-tcmr) Provoked a Broadened Alloimmune Responsementioning
confidence: 97%
See 1 more Smart Citation
“…In addition, it must be mentioned that in patients with high‐level viremia, the eGFR was already inferior 3 months after transplantation and rejection episodes were more frequent compared with the other groups. In the context of eGFR and graft rejection as a predictor of graft outcome and eGFR decline, this could mean that these grafts were already compromised or impaired by rejection early after transplantation, which is a limitation of this study.…”
Section: Discussionmentioning
confidence: 97%
“…A retrospective study conducted in the United States on re-transplant patients receiving rabbit-derived antithymocyte globulin (rATG) induction therapy [15] showed relatively low rates of acute rejections in both the steroid withdrawal and triple therapy groups. While these and other studies tend to show non-inferiority of steroidfree maintenance regimens in low risk patients -and perhaps a hint that in higher risk patients receiving induction therapy early withdrawal may be safe -it remains unclear whether the improvements in metabolic complications, including new onset diabetes [16] , skeletal complications including fracture risk [17] are sufficiently counterbalancing the risk for long-term immunological [18] and increased rates for DSA [19] in this setting. On the other hand, the possibility of increased risk for antibody-mediated rejection after steroid withdrawal in high-risk populations is currently not sufficiently explored.…”
Section: Glucocorticoidsmentioning
confidence: 89%